Linkage between national social care and education data for unaccompanied asylum-seeking children in England, 2005-2021 - Langella, Rebecca; Lewis, Kate; Hardelid, Pia (International Journal of Population Data Science, 2025)
Unaccompanied Asylum-Seeking Children (UASCs) constitute one of the most vulnerable populations in the UK, often experiencing ongoing hardship. This study aimed to describe the UASCs population within the Children Looked After (CLA) dataset and to describe the association between socio-demographic characteristics and attendance at state-funded schools in England. We used national, linked social care-hospital administrative data from the ECHILD database from 2005 to 2021. The UASC population was identified using the UASC flag which was already included in the social care dataset. We described the UASCs population and their linkage to National Pupil Dataset (NPD) by data, by gender, age group, ethnicity of placement type. The CLA dataset included 38,8820 UASCs in the study period. The majority were male (86%,33730/38820), aged 16 and over at placement (66%,25530/38820). Only 1/10 were from a White ethnic background (10%,3870/38820). Two in five UASCs were placed in foster care (care of strangers, 41%, 16000/38820), and half in unregulated and independent accommodations (50%,10280/38820). Less than 22% of UASCs (8600/38820) in the social care dataset were linkable to NPD. Linkage rates to the NPD dataset were lower for UASCs who were aged 16 and over (6%,1480/25340), Black (17%,1890/10910), or placed in unregulated and independent accommodations (11%,1370/19270). This paper is the first to evaluate linkage between national social care and education databases for UASCs in England. Less than a quarter of UASCs could be linked to education data. This reduces our capacity to link UASCs to other datasets included within ECHILD, such as Hospital Episode Statistics (HES).